Pivoting Your Small Business in a Crisis. - Gassner, David; Kennedy, Ashley; Rand-Hendriksen, Morten; Bennett, Sharon; Maestri, George; Chow, Garrick; Stratton, Jess (linkedin.com, 2020)
Keeping your business afloat and your customers satisfied during a global pandemic is no easy feat. Tune into this course to get practical tips for finding the right path forward.